2023
DOI: 10.3847/1538-3881/acdb70
|View full text |Cite
|
Sign up to set email alerts
|

The MUSCLES Extension for Atmospheric Transmission Spectroscopy: UV and X-Ray Host-star Observations for JWST ERS & GTO Targets

Abstract: X-ray through infrared spectral energy distributions (SEDs) are essential for understanding a star’s effect on exoplanet atmospheric composition and evolution. We present a catalog of panchromatic SEDs, hosted on the Barbara A. Mikulski Archive for Space Telescopes, for 11 exoplanet-hosting stars that have guaranteed JWST observation time as part of the ERS or GTO programs but have no previous UV characterization. The stars in this survey range from spectral type F4-M6 (0.14–1.57 M ☉), rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 137 publications
1
4
0
Order By: Relevance
“…Using the ATES model grid from Caldiroli et al (2022), we calculated a predicted massloss rate of  = Ḿ 7.3 10 10 g s −1 . This is in good agreement with Edwards et al (2023), who also used the MUSCLES spectrum from Behr et al (2023) and predicted a mass-loss rate of  » M 10 11 g s −1 with a detailed outflow model based on Allan & Vidotto (2019). These mass-loss rates are ruled out by our observations at the 95% level.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Using the ATES model grid from Caldiroli et al (2022), we calculated a predicted massloss rate of  = Ḿ 7.3 10 10 g s −1 . This is in good agreement with Edwards et al (2023), who also used the MUSCLES spectrum from Behr et al (2023) and predicted a mass-loss rate of  » M 10 11 g s −1 with a detailed outflow model based on Allan & Vidotto (2019). These mass-loss rates are ruled out by our observations at the 95% level.…”
Section: Discussionsupporting
confidence: 89%
“…Using an isothermal Parker wind model, we found the planetary mass-loss rate to be <10 10.03 g s −1 and <10 11.11 g s −1 at the 95th and 99.7th percentiles, respectively. Our model accounted for the relatively low XUV luminosity of LTT 9779, which certainly contributes to the non-detection (Behr et al 2023;Fernández Fernández et al 2024). Even so, our inferred mass-loss rate is at least a factor of a few smaller than predicted by photoevaporation models that assume a pure H/He composition for the planetary envelope (Kubyshkina et al 2018;Caldiroli et al 2022;Edwards et al 2023;Fernández Fernández et al 2024).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is unclear what differentiates the planet-hosting systems with higher flare rates from the control sample. France et al (2018) and Behr et al (2023) found that planet-hosting stars are less active than an equivalent control sample of field-age stars in the UV. In Figure 9 the color of the points corresponds to the effective temperature of the star.…”
Section: Flare Rates Of Young Planet Host Stars Versus Comparison Samplementioning
confidence: 99%
“…exoplanet mass-loss rates derived with proxy stellar spectra from another star are similarly uncertain (Behr et al 2023). Compounding the issue, the X-ray output from a given star is often time variable (Wagner 1988;Woods & Rottman 2005;Chadney et al 2015) and should alter exoplanetary atmospheric conditions accordingly (Wang & Dai 2021).…”
Section: Introductionmentioning
confidence: 99%